Human nature and his potentialities attributes towards virtue and morality - Ali, Md Yousuf (Journal of Education and Social Science (JESOC), 2016)
Human nature (fitrah) is an innate or in-born spiritual quality of man in human life. While his potentialities have been used by righteous people as means for improving his/her good moral quality, these have been largely practiced by evildoers for their own interest. Instances of the contribution of his innate potential qualities can be found in the context of the prophets, righteous and pious people in human history because every child is born in a state of fitrah, then his parents make him a Jew, a Christian or a Muslim. In contemporary time, a secular man is greatly influenced by the anti-religious trends within secular modernity in terms of belief, value and action, which are a violation of his in-born natural quality. In these situations, realizing his potentialities in contemporary context to be a good moral is an essential for establishing value-based human society.This paper therefore examines the meaning of man’s fitrah and the role of his potentialities and analyzes these within the purview of contemporary thought, which is based on the textual arguments of the Qur`an and Sunnah. The paper concludes that though some Muslims go against their fitrah and potentialities, the majority of the Muslim scholars have viewed human fitrah and his potentialities as means for developing man’s high good moral quality.